PENGARUH KEPEMIMPINAN, KEPUASAN KERJA, DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. PADI MANDIRI VALUTA DENPASAR - I Kadek Yayang Arta Sentana; I Gede Rihayana; Bagus Nyoman Kusuma Putra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Employee performance is very important in the success of a company, one of which is by good leadership, providing employee job satisfaction and maintaining employee work competence. The purpose of this study is to determine the influence of leadership, job satisfaction and competence on the performance of PT. Padi Mandiri Valuta Denpasar. The location of this research was conducted at PT. Padi Mandiri Valuta Denpasar with a sample of 30 respondents. The sampling method used in this study is a nonprobability sampling method in the form of saturated sampling. The data analysis techniques used are multiple linear regression analysis, determination coefficient test, F test and t test. The results of this study found that leadership has a positive and significant effect on employee performance which means better leadership. Job satisfaction has a positive and significant effect on employee performance. Competency has a positive and significant effect on employee performance. Suggestions that can be given in this study are the leaders of PT. Padi Mandiri Valuta Denpasar in order to always be able to provide motivation or enthusiasm for all employees so that they can do work with maximum results, provide job training to employees, and provide traning in advance to prospective employees.